Influence of no-core fiber on the focusing performance of an ultra-small gradient-index fiber probe. (August 2018) - Bi, Shubo; Wang, Chi; Zhu, Jun; Yuan, Zhiwen; Yu, Yingjie; Valyukh, Sergiy; Asundi, Anand
Highlights: Effective beam expansion range of no-core fiber length in an ultra-small Gradient-index fiber probe is proposed. Verifying calculation method of effective beam expansion length of no-core fiber. Analyzing the influence of no-core fiber on focusing performance of GRIN fiber probes. Optimizing the structure of the ultra-small Gradient-index fiber probe. Abstract: The light-beam expansion effect of a no-core fiber on the focusing performance of an ultra-small gradient-index fiber probe is investigated with a view to optimizing the optical performance of such probes. By taking the variable relationship between the focusing performance (including the working distance and the focusing spot size) of the probe and the length of the no-core fiber as the criterion, the effective beam expansion length of the no-core fiber in the ultra-small gradient-index fiber probe is calculated based on the basic properties of the Gaussian beam. Verification and analysis are done by numerical calculations and experimental measurements, respectively. The obtained results show that the working distance of an ultra-small gradient-index fiber probe can be increased effectively by adding a no-core fiber; however, this will lead to increasing the focusing spot size. For the parameters of the fiber probe studied here, the effective beam expansion length of the no-core fiber spacer is less than 0.357 mm.